If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 2) + -2(x + 4) = 7 Reorder the terms: (2 + 3x) + -2(x + 4) = 7 Remove parenthesis around (2 + 3x) 2 + 3x + -2(x + 4) = 7 Reorder the terms: 2 + 3x + -2(4 + x) = 7 2 + 3x + (4 * -2 + x * -2) = 7 2 + 3x + (-8 + -2x) = 7 Reorder the terms: 2 + -8 + 3x + -2x = 7 Combine like terms: 2 + -8 = -6 -6 + 3x + -2x = 7 Combine like terms: 3x + -2x = 1x -6 + 1x = 7 Solving -6 + 1x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 1x = 7 + 6 Combine like terms: -6 + 6 = 0 0 + 1x = 7 + 6 1x = 7 + 6 Combine like terms: 7 + 6 = 13 1x = 13 Divide each side by '1'. x = 13 Simplifying x = 13
| 10x+9=7+27 | | 12x-3=131 | | 106-6x=3x+7 | | 2x+12=66-4 | | 3x+5(2-x)=-16 | | (6x^2-12x-18)(x-1)=0 | | -2u-2=14 | | 4+7x=180 | | -3u+(-6)=21 | | y-8=2(x-1) | | -2c-7=-5 | | 5y=2y+18 | | -2c+7=27 | | 8(u+2)=-3u+5 | | -3=-2x-46 | | y-180=5(x-20) | | 7x+3=2x+12 | | y-55=5(x-10) | | 5y^2=40 | | y-60=-9(x-20) | | 950000000=104(x)-207474 | | 4r^2=36r | | 3(x-12)= | | 3x^2+x=24 | | 6+2x(x-3)=2x^2 | | -2a-(-9)=23 | | 3(x+12)= | | -3(x+12)= | | (x-1)(x-3)(x+2)(x+4)+24= | | (x)(2x^2+9x+10)= | | 5+2(k+4)=5(k+3)+10 | | 9x^2+2x^3= |